Role of laboratory testing in the diagnosis of acute viral rhinitis: A Narrative Review - Kemal Hanief Al Ghifari; Naysa Maharani Putri; Ayudya Dimas Rizky Utama; Renata Aurellia Laksita; Farah Najma Haristsah; Metana Puspitasari (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Acute viral rhinitis is one of the most prevalent upper respiratory conditions, primarily caused by rhinovirus, with other viruses such as coronavirus, adenovirus, RSV, and influenza contributing to smaller proportions. Although diagnosis is typically clinical, laboratory testing plays an increasingly important role in distinguishing between viral and bacterial etiologies, preventing unnecessary antibiotic use, and enhancing clinical decision-making. Methods: A literature search was conducted using PubMed and Google Scholar for articles published from 2020 to 2025. Keywords included “Acute Viral Rhinitis,” “Common Cold,” “Laboratory Diagnosis,” “Multiplex PCR,” and “Point-of-Care Test.” From 89 initially identified studies, screening based on inclusion and exclusion criteria resulted in nine eligible publications. These were synthesized using a narrative review approach and evaluated using the SANRA instrument. Results: Molecular diagnostic methods such as RT-PCR and multiplex PCR demonstrated the highest diagnostic accuracy (>95%) for detecting respiratory viral pathogens. Classic immunological tests, including skin prick testing and ImmunoCAP, remain relevant for assessing allergic rhinitis but are less useful for differentiating between viral and bacterial infections. Basic biomarkers such as CRP and procalcitonin provided moderate sensitivity and supported early clinical screening. Emerging point-of-care tests, particularly assays measuring MxA and CRP, have shown promising accuracy in distinguishing between viral and bacterial infections, making them valuable for primary care settings. Conclusion: No single laboratory method is ideal for diagnosing acute viral rhinitis. A combined approach integrating classical, molecular, and point-of-care diagnostics enhances diagnostic precision and promotes rational antibiotic stewardship. Future practice should prioritize wider access to molecular testing, the adoption of validated point-of-care tools, and the continued development of novel biomarkers to enhance rapid and accurate diagnosis in diverse clinical settings.